Cathode material, composite cathode material, cathode sheet, preparation method and lithium ion power battery
Patent Information
- Application Number
- CN202411994519.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-12-31
AI Technical Summary
该方法虽然能提高锂离子电池能量密度,但金属锂反应活性高,极易与空气中的氧气及水分发生反应,工艺难度过大
[0044] (1) This invention provides a cathode material for lithium-ion power batteries. The chemical composition of this cathode material is mainly composed of nickel-cobalt-manganese ternary materials and lithium manganese iron phosphate, and is doped with elements M and A. The main function of element M is to stabilize the crystal structure by forming strong MO bonds, reduce the generation of oxygen vacancies, suppress phase transitions and Li/Ni mixing, and simultaneously promote Li… + Migration; the main role of element A is to improve the ionic conductivity and diffusion performance of the material from within the crystal lattice, and to suppress the Jan Taylor effect. This cathode material combines the advantages of both ternary and lithium manganese iron phosphate materials, integrating high specific capacity (220–280 mAh/g), high cycle stability, and high safety, improving the dual voltage plateau, thereby significantly increasing energy density. Compared with ternary materials, it can significantly improve cycle performance and safety performance.
Smart Images

Figure CN119786576B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery material technology, and relates to a cathode material, a composite cathode material, a cathode sheet and its preparation method, and a lithium-ion power battery. Background Technology
[0002] In recent years, with the continuous development and maturation of the new energy vehicle market, users' demands for longer driving ranges have become increasingly strong, thus creating an urgent need for higher energy density lithium-ion batteries to meet market demands. At the same time, the usage scenarios for new energy vehicles are becoming increasingly diverse, and the environments and conditions faced by power batteries are becoming increasingly harsh, such as high and low temperature discharge, cycling, and storage, which places higher demands on the lifespan of lithium-ion batteries. Furthermore, retired lithium-ion batteries from new energy vehicles can be reused in logistics vehicles, base stations, communications, and building backup power supplies through a tiered utilization approach, thus requiring further improvement in the lifespan of lithium-ion batteries.
[0003] However, the most mainstream power lithium-ion battery in the industry is still the lithium iron phosphate battery, with a general energy density of 160-180Wh / kg. A few battery manufacturers with strong R&D capabilities can increase the energy density to over 190Wh / kg. But ultimately, even excluding the influence of negative electrode materials, current collectors, binders, conductive agents, electrolytes, etc., it is difficult to reach the limit target of lithium iron phosphate (≥200Wh / kg). In addition, another common positive electrode material for power batteries is ternary material. Although this material has higher energy density, better high-rate charge and discharge performance, and low-temperature performance, its cycle performance is not as good as lithium iron phosphate, and its safety performance is poor and its cost is high, which is not conducive to the further development of enterprises and the new energy industry. When batteries are used under harsh conditions for a long time, by-products accumulate and block the electrode sheets and separator pores due to electrode shrinkage and expansion, particle pulverization, and various side reactions related to electrolytes inside the cell. The SEI film of the negative electrode is damaged and thickened, accompanied by gas production, etc., which eventually leads to cell cycle failure, lithium plating, and various failures, thus affecting the actual energy density and service life of the power battery.
[0004] To improve the energy density and lifespan of power batteries, a common method is lithium replenishment technology. For example, slurry-based lithium replenishment involves mixing metallic lithium or lithium-containing organic compounds, modified materials, and non-aqueous liquids to form a slurry, which is then coated onto a current collector to create an electrode. While this method can increase the energy density of lithium-ion batteries, metallic lithium is highly reactive and readily reacts with oxygen and moisture in the air, making the process extremely difficult. Alternatively, lithium-rich lithium salts, lithium oxides, or lithium-containing organic compounds can be used for lithium replenishment at the positive electrode. However, due to issues with the activity and utilization rate of these materials, practical application faces significant challenges. Furthermore, to improve battery safety, most battery manufacturers optimize the design of battery separators, electrolytes, and structural dimensions to achieve rapid heat dissipation, short-circuit protection, and pressure relief, thereby reducing the risk of thermal runaway to some extent. However, this does not fundamentally solve the safety issues of charging and discharging lithium batteries under extreme conditions, which involves the intrinsic safety and thermal stability of the positive electrode material.
[0005] In view of this, the present invention is hereby proposed. Summary of the Invention
[0006] To address the bottlenecks encountered in significantly improving the energy density of lithium iron phosphate batteries in the current power battery field and to reduce the impact of internal battery side reaction products on energy density and lifespan, this invention aims to provide a cathode material, a composite cathode material, a cathode sheet, a preparation method, and a lithium-ion power battery.
[0007] To achieve the above objectives, the following technical solution is adopted:
[0008] The primary objective of this invention is to provide a cathode material for lithium-ion power batteries, wherein the general formula of the cathode material is:
[0009] Li2(Ni a Co b Mn c ) 1-d M d O2·Mn x Fe y PO4·A;
[0010] Where a+b+c=1, and 0<a≤0.6, 0<b≤0.1, 0<c<0.4, 0<d≤0.01, and M is selected from at least one of the elements Cu, Al, W, Ti, Sr, Sb, Nb, Mg, Zr, Zn, La, Y, S, N, B or F;
[0011] x+y=1, and 0<x<1, 0<y<1, x:y=(0.2~0.8):(0.8~0.2); the A is selected from at least one of the elements Mg, Zn, Cu, Co, Ni, Cr, V, Ti, Zr or C.
[0012] Furthermore, based on the above-mentioned technical solution of the present invention, the particle size of the positive electrode material is 5-30 μm;
[0013] And / or, the specific surface area of the positive electrode material is 1–40 m². 2 / g;
[0014] And / or, the cathode material is made of a nickel-cobalt-manganese ternary precursor, a lithium manganese iron phosphate precursor, and a first dopant containing element M and a second dopant containing element A;
[0015] The second objective of this invention is to provide a method for preparing the above-mentioned cathode material, which is prepared using either method one or method two:
[0016] Method 1: Mix nickel-cobalt-manganese ternary precursor and lithium manganese iron phosphate precursor in a certain proportion to obtain a composite precursor;
[0017] A first dopant containing element M and a second dopant containing element A are added to the composite precursor, followed by sintering to obtain the cathode material; or,
[0018] Method 2: Add a first dopant containing element M during the preparation of nickel-cobalt-manganese ternary material precursor to obtain nickel-cobalt-manganese ternary material precursor doped with element M;
[0019] In the process of preparing lithium manganese iron phosphate precursor, a second dopant containing element A is added to obtain an A-doped lithium manganese iron phosphate precursor.
[0020] A nickel-cobalt-manganese ternary precursor doped with element M and a lithium manganese iron phosphate precursor doped with element A are mixed in a certain proportion and then sintered to obtain the cathode material.
[0021] Furthermore, based on the above-mentioned technical solution of the present invention, in Method 1, the particle size of the nickel-cobalt-manganese ternary material precursor is 1-15 μm; and / or, the particle size of the lithium manganese iron phosphate precursor is 100-400 nm.
[0022] And / or, in Method 1, the mass ratio of the nickel-cobalt-manganese ternary precursor to the lithium manganese iron phosphate precursor is (0.2-0.8):(0.8-0.2);
[0023] And / or, in method one, the first dopant accounts for 1 to 2% of the mass fraction of the composite precursor;
[0024] And / or, in method one, the mass ratio of the first dopant to the second dopant is (0.2~0.8):(0.8~0.2);
[0025] And / or, in Method 2, the mass ratio of the nickel-cobalt-manganese ternary precursor doped with element M to the lithium manganese iron phosphate precursor doped with element A is (0.2-0.8):(0.8-0.2);
[0026] And / or, in Method 2, the first dopant accounts for 2-3% of the mass fraction of the nickel-cobalt-manganese ternary precursor;
[0027] And / or, in Method 2, the second dopant accounts for 1-3% of the mass fraction of the lithium manganese iron phosphate precursor;
[0028] And / or, in Method 1 and Method 2, the sintering temperature is 600-800℃, the sintering time is 3-12h, and the sintering atmosphere is nitrogen or helium.
[0029] The third objective of this invention is to provide a composite cathode material for lithium-ion power batteries, comprising the cathode material provided in the first objective of this invention and a coating layer covering the surface of the cathode material;
[0030] The coating layer is mainly made of composite additives, which include at least two substances selected from lithium bis(fluorosulfonyl)imide, 2-allylphenoxytrimethylsilane, Lewis base, or compounds containing N / B elements.
[0031] Furthermore, based on the above technical solution of the present invention, the thickness of the coating layer is 5-50 nm;
[0032] And / or, the mass ratio of the composite additive to the positive electrode material is (1-50):100, preferably (5-20):100;
[0033] And / or, the Lewis base includes at least one of N-dimethylamide and N-acetylcaprolactam;
[0034] And / or, the N / B-containing compounds include N-containing compounds and / or B-containing compounds, the N-containing compounds include nitrile compounds and / or amine compounds, and the B-containing compounds include borate esters and / or borane compounds.
[0035] The fourth objective of this invention is to provide a method for preparing a composite cathode material, comprising the following steps: physically blending a composite additive and a cathode material, and then drying the mixture to obtain the composite cathode material.
[0036] The fifth objective of this invention is to provide a positive electrode sheet, comprising a current collector and a positive electrode material layer formed on the surface of the current collector;
[0037] The positive electrode material layer includes: a conductive agent, a binder, and the positive electrode material provided by the first objective of this invention or the composite positive electrode material provided by the third objective of this invention.
[0038] The sixth objective of this invention is to provide a method for preparing a positive electrode sheet, using one, two, or three of the following methods:
[0039] Method 1: Prepare a slurry by combining the conductive agent, binder, and positive electrode material or composite positive electrode material, coat it on the surface of the current collector, and dry it to obtain a positive electrode sheet;
[0040] Method 2: The positive electrode material, composite additive, conductive agent and binder are made into a slurry, coated on the surface of the current collector, and dried to obtain a positive electrode sheet;
[0041] Method 3: Prepare a slurry by combining positive electrode material, conductive agent and binder, coat it on the surface of the current collector, then spray a composite additive on the surface of the current collector positive electrode material layer, and dry it to obtain a positive electrode sheet.
[0042] The seventh objective of this invention is to provide a lithium-ion power battery, comprising the positive electrode material provided by the first objective of this invention, the composite positive electrode material provided by the third objective of this invention, or the positive electrode sheet provided by the fifth objective of this invention.
[0043] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:
[0044] (1) This invention provides a cathode material for lithium-ion power batteries. The chemical composition of this cathode material is mainly composed of nickel-cobalt-manganese ternary materials and lithium manganese iron phosphate, and is doped with elements M and A. The main function of element M is to stabilize the crystal structure by forming strong MO bonds, reduce the generation of oxygen vacancies, suppress phase transitions and Li / Ni mixing, and simultaneously promote Li… + Migration; the main role of element A is to improve the ionic conductivity and diffusion performance of the material from within the crystal lattice, and to suppress the Jan Taylor effect. This cathode material combines the advantages of both ternary and lithium manganese iron phosphate materials, integrating high specific capacity (220–280 mAh / g), high cycle stability, and high safety, improving the dual voltage plateau, thereby significantly increasing energy density. Compared with ternary materials, it can significantly improve cycle performance and safety performance.
[0045] (2) The present invention also provides a composite cathode material for lithium-ion power batteries, including the cathode material provided by the present invention and a coating layer coated on the surface of the cathode material. The coating layer is mainly made of a specific type of composite additive. The composite additive can form a nanoscale interface protective film (coating layer) on the surface of the cathode material particles. Its main components do not react chemically with the electrolyte. During the actual charging and discharging process of the battery, it will preferentially react with HF generated by the oxidation and decomposition of the electrolyte, and transfer F ions to the high-fluorine interface film. This not only eliminates HF in the electrolyte, but also improves the stability of the interface film. At the same time, it inhibits the dissolution of transition metal ions and reduces the generation of by-products, which can significantly improve the cycle performance of high-energy-density composite cathode materials. Attached Figure Description
[0046] Figure 1 This is a schematic diagram of the composite precursor preparation process provided by the present invention;
[0047] Figure 2 This is a schematic diagram of the cathode material preparation process provided by the present invention;
[0048] Figure 3 This is a schematic diagram of the composite cathode material preparation process provided by the present invention. Detailed Implementation
[0049] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention. Process parameters not specifically specified in the following embodiments are generally performed under conventional conditions.
[0050] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0051] According to a first aspect of the present invention, a positive electrode material for a lithium-ion power battery is provided, the general formula of which is:
[0052] Li2(Ni a Co b Mn c ) 1-dM d O2·Mn x Fe y PO4·A;
[0053] Where a+b+c=1, and 0<a≤0.6, 0<b≤0.1, 0<c<0.4, 0<d≤0.01, and M is selected from at least one of the elements Cu, Al, W, Ti, Sr, Sb, Nb, Mg, Zr, Zn, La, Y, S, N, B or F;
[0054] x+y=1, and 0<x<1, 0<y<1, x:y=(0.2~0.8):(0.8~0.2); the A is selected from at least one of the elements such as Mg, Zn, Cu, Co, Ni, Cr, V, Ti, Zr or C.
[0055] The chemical composition of this cathode material is mainly composed of nickel-cobalt-manganese ternary materials and lithium manganese iron phosphate, with doping of elements M and A. The M element is primarily doped or coated within the ternary material, existing mainly as high-valence metal ions or non-metal ions. Its main function is to stabilize the crystal structure by forming strong M-O bonds, reducing oxygen vacancy generation, suppressing phase transitions and Li / Ni mixing, and simultaneously promoting Li... + Migration; Element A is mainly doped or coated in lithium manganese iron phosphate, primarily existing as metal ions or non-metallic element C. Its main function is to improve the ionic conductivity and diffusion performance of the material from within the crystal lattice, and to suppress the Jan Taylor effect. C coating elements can improve the electronic conductivity of the material and reduce side reactions with the electrolyte. This cathode material combines the advantages of both ternary and lithium manganese iron phosphate, integrating high specific capacity (220–280 mAh / g), high cycle stability, and high safety, improving the dual voltage plateau, thereby significantly increasing energy density. Compared with ternary materials, it significantly improves cycle performance and safety performance. It should be noted that although element M is mainly doped or coated in ternary materials and element A is mainly doped or coated in lithium manganese iron phosphate, there may be cases where some element M is doped or coated in lithium manganese iron phosphate and some element A is doped or coated in ternary materials. This situation has little impact on the overall performance of the cathode material, because M and A elements, as dopants, can interpenetrate in the composite precursor, thus having a synergistic gain effect in the cathode material.
[0056] In the general formula, b represents the content of Co element. Limiting it to a specific value range is mainly to improve the energy density of the material while taking into account the stability and safety of the material cycle. Typical but non-limiting values of b are 0.01, 0.02, 0.04, 0.05, 0.06, 0.08, or 0.1, etc. d represents the content of doped or coated M element. Limiting it to a specific value range can improve the conductivity and kinetic properties of the material while ensuring its performance. Typical but non-limiting values of d are 0.002, 0.005, 0.008, or 0.01, etc. In addition, limiting the ratio range between x and y is beneficial for preparing precursors or materials of lithium manganese iron phosphate with different performance characteristics. It can be adjusted according to actual needs. Typical but non-limiting x:y ratios are 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3, or 0.8:0.2, etc.
[0057] As an optional embodiment of the present invention, the particle size of the positive electrode material is 5 to 30 μm, and typical but non-limiting particle sizes are 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., and any numerical range between any two points.
[0058] As an optional embodiment of the present invention, in the general formula of the positive electrode material, M is selected from at least one of elements such as Nb, Al, B or F, and A is selected from at least one of elements such as Mg, Cu or C.
[0059] As an optional embodiment of the present invention, the cathode material is made of a nickel-cobalt-manganese ternary material precursor, a lithium manganese iron phosphate precursor, a first dopant containing element M, and a second dopant containing element A.
[0060] As an optional embodiment of the present invention, the specific surface area of the cathode material is 1–40 m². 2 / g, for example, 1m 2 / g、5m 2 / g, 10m 2 / g、20m 2 / g、30m 2 / g or 40m 2 / g etc.
[0061] The preparation methods for nickel-cobalt-manganese ternary material precursors and lithium manganese iron phosphate precursors are not specifically limited, and can be obtained using conventional chemical or physical preparation methods in this field. Chemical preparation methods include, but are not limited to, high-temperature solid-state methods, carbothermal reduction methods, hydrothermal methods, co-precipitation methods, pulsed laser deposition methods, and sol-gel methods. Physical preparation methods include, but are not limited to, high-energy ball milling, physical vapor deposition methods, and high-speed mixing methods.
[0062] In the preparation of nickel-cobalt-manganese ternary material precursors and lithium manganese iron phosphate precursors, the lithium source selected includes one or more of Li2CO3, LiOH, Li2O, CH3COOLi, LiNO3, and Li2C2O4; the nickel source, manganese source, and cobalt source in the ternary material are, for example, nickel sulfate, manganese sulfate, and cobalt sulfate; the manganese source in lithium manganese iron phosphate includes one or more of manganese sulfate, manganese carbonate, or manganese hydroxide, and the iron source includes one or more of FePO4, Fe2O3, FeOOH, Fe(OH)3, Fe(NO3)3, and Fe2(SO4)3.
[0063] As an optional embodiment of the present invention, the particle size of the nickel-cobalt-manganese ternary material precursor is 1 to 15 μm, and typical but non-limiting particle sizes are 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm or 15 μm, etc., as well as the numerical range between any two points.
[0064] As an optional embodiment of the present invention, the particle size of the lithium manganese iron phosphate precursor is 100-400 nm, and typical but non-limiting particle sizes are 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm or 400 nm, etc., and any numerical range between any two points.
[0065] In an optional embodiment of the present invention, the first dopant is mainly used to provide element M. When element M is a metallic element, the raw material form of the first dopant can be cation-containing (Cu) 2+ 、Nb 5+ Mg 2+ Zn 2+ La 3+ B 3+ Y 3+ Compounds of metals such as phosphates, acetates, nitrates, etc., or metal oxides (Al₂O₃, ZrO₂, WO₃, TiO₂, etc.); M is a nonmetallic element (F...). - S 2- When (etc.), it can be a sulfide, fluoride, etc.
[0066] In an optional embodiment of the present invention, the second dopant is mainly used to provide element A, wherein A is selected from Mg. 2+ Zn 2+ Cu 2+ Co 3+ Ni 2+ Cr 3+ V 3+ Ti 4+ Zr 4+ Or at least one of C. When element A is a metallic element, the raw material form of the second dopant can be cation-containing (Mg) 2+ Zn2+ Cu 2+ Ni 2+ Cr 3+ Compounds such as phosphates, acetates, nitrates, etc., or metal oxides (Co2O3, ZrO2, V2O3, TiO2, etc.); when M is a non-metallic element C, its raw material form can be sugars, such as glucose, sucrose, starch, etc., or organic polymers, such as polyvinyl alcohol (PVA), polyethylene glycol, etc., or small molecule organic compounds, such as citric acid, oxalic acid, vitamin C, etc.
[0067] According to a second aspect of the present invention, a method for preparing the cathode material provided in the first aspect of the present invention is also provided, wherein the material is prepared using either method one or method two as follows:
[0068] Method 1: A composite precursor is obtained by mixing nickel-cobalt-manganese ternary material precursor (NCM precursor) and lithium manganese iron phosphate precursor (LMFP precursor) in a certain proportion;
[0069] A first dopant containing element M and a second dopant containing element A are added to the composite precursor, followed by sintering to obtain the cathode material. A schematic diagram of the preparation process is shown below. Figure 1 and Figure 2 As shown; or,
[0070] Method 2: Add a first dopant containing element M during the preparation of nickel-cobalt-manganese ternary material precursor to obtain nickel-cobalt-manganese ternary material precursor doped with element M;
[0071] In the process of preparing lithium manganese iron phosphate precursor, a second dopant containing element A is added to obtain an A-doped lithium manganese iron phosphate precursor.
[0072] A nickel-cobalt-manganese ternary precursor doped with element M and a lithium manganese iron phosphate precursor doped with element A are mixed in a certain proportion and then sintered to obtain the cathode material.
[0073] The first dopant (corresponding to element M) and the second dopant (corresponding to element A) can be added during the sintering process of the composite precursor. This method has a simple synthesis process, high production efficiency, and low cost.
[0074] The first dopant (corresponding to element M) and the second dopant (corresponding to element A) can also be added before sintering, i.e. during the synthesis of the precursor. The chemical methods used to synthesize the precursor include conventional solid-phase methods or liquid-phase methods. Solid-phase methods include high-temperature solid-phase reaction methods, carbothermal reduction methods, microwave synthesis methods, etc.; liquid-phase methods include sol-gel methods, hydrothermal synthesis methods, etc. This method makes the doping and coating highly efficient, uniform, and stable in structure and performance.
[0075] As an optional embodiment of the present invention, in method one, the mass ratio of the nickel-cobalt-manganese ternary material precursor to the lithium manganese iron phosphate precursor is (0.2-0.8):(0.8-0.2); typical but non-limiting mass ratios are 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3, or 0.8:0.2, etc.
[0076] The relative amounts of the first dopant and the second dopant are determined based on the ratio of the nickel-cobalt-manganese ternary precursor to the lithium manganese iron phosphate precursor. As an optional embodiment of the present invention, the mass ratio of the first dopant to the second dopant is (0.2–0.8):(0.8–0.2). For example, the mass ratio of the first dopant to the second dopant is 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.6:0.4, 0.7:0.3, or 0.8:0.2, etc.
[0077] In a preferred embodiment of the present invention, in method one, the first dopant accounts for 1-2% of the mass fraction of the composite precursor (nickel-cobalt-manganese ternary material precursor and lithium manganese iron phosphate precursor), for example, 1%, 1.2%, 1.5%, 1.6%, 1.8%, or 2%; and / or,
[0078] The second dopant accounts for 0.5% to 2% of the mass fraction of the composite precursor (nickel-cobalt-manganese ternary material precursor and lithium manganese iron phosphate precursor), for example, 0.5%, 0.75%, 1%, 1.2%, 1.5%, 1.6%, 1.8% or 2%, etc.
[0079] As an optional embodiment of the present invention, in method two, the mass ratio of the nickel-cobalt-manganese ternary precursor doped with element M to the lithium manganese iron phosphate precursor doped with element A is (0.2-0.8):(0.8-0.2), for example, 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3, or 0.8:0.2, etc.
[0080] As an optional embodiment of the present invention, in method two, the first dopant accounts for 2-3% of the mass fraction of the nickel-cobalt-manganese ternary precursor, for example, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, or 3%; and / or,
[0081] In Method 2, the second dopant accounts for 1-3% of the mass fraction of the lithium manganese iron phosphate precursor, for example, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, or 3%.
[0082] As an optional embodiment of the present invention, in methods one and two, the sintering temperature is 600–800°C, and the sintering time is 3–12 hours. Typical but non-limiting sintering temperatures include 600°C, 650°C, 700°C, 750°C, or 800°C, and any range between any two points; typical but non-limiting sintering times include 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours, or 12 hours, and any range between any two points.
[0083] As an optional embodiment of the present invention, in Method 1 and Method 2, the sintering atmosphere is nitrogen or helium, etc.
[0084] According to a third aspect of the present invention, a composite cathode material for lithium-ion power batteries is provided, comprising the cathode material provided in the first aspect of the present invention and a coating layer covering the surface of the cathode material;
[0085] The coating layer is mainly made of composite additives, which include at least two substances selected from lithium bis(fluorosulfonyl)imide (LiFSI), 2-allylphenoxytrimethylsilane, Lewis base, or compounds containing N / B elements.
[0086] An appropriate amount of lithium bis(fluorosulfonyl)imide salt can improve the ionic conductivity of the material in the electrolyte. In addition, it can enhance the thermal stability and electrochemical window of the composite additive; improve the interfacial film performance; inhibit HF generation; and improve cycle life, rate capability, and safety.
[0087] 2-Allylphenoxytrimethylsilane can effectively form a complex with HF in the electrolyte and preferentially form an interfacial protective film on the positive electrode surface compared with ester solvents, which allows F ions to transfer to the interfacial film and improves the stability of the interfacial film.
[0088] Lewis bases, such as amide additives (e.g., N-acetylcaprolactam), can have strong complexing effects with PF5, HF, or H2O.
[0089] In compounds containing N / B elements, the " / " signifies "and / or," meaning it can be a compound containing N, a compound containing B, or both. Compounds containing N can modulate the solvation structure of ions in the electrolyte, facilitating the transport of Li ions. During charge and discharge, they can participate in the formation of a solid electrolyte film on the electrode surface, reducing side reactions. Compounds containing B can stabilize the electrode structure, regulate interfacial chemistry, inhibit HF formation, and improve high-temperature performance.
[0090] Composite additives can form a nanoscale interfacial protective film (coating layer) on the surface of cathode material particles. Its main components do not chemically react with the electrolyte. During the actual charging and discharging process of the battery, it will preferentially react with HF generated by the oxidation and decomposition of the electrolyte, transferring F ions to the high-fluorine interfacial film. This not only eliminates HF in the electrolyte but also improves the stability of the interfacial film. At the same time, it inhibits the dissolution of transition metal ions (mainly from the synthesized cathode materials, such as Ni ions, Co ions, Mn ions in ternary materials and Mn ions in lithium manganese iron phosphate), reduces the generation of by-products, and significantly improves the cycle performance of high-energy-density composite cathode materials.
[0091] Composite additives can continuously consume the HF in the electrolyte and inhibit the generation of by-products, thereby improving the stability of the SEI film at the negative electrode interface to a certain extent, while reducing the accumulation of by-products in the later stages of cycling and thus reducing pore blockage.
[0092] In a preferred embodiment of the present invention, the composite additive includes lithium bis(fluorosulfonyl)imide and 2-allylphenoxytrimethylsilane. In addition, Lewis bases or compounds containing N / B elements (inorganic salts) may also be added.
[0093] Composite additives can form a nanoscale fluorine-containing protective film on the surface of the cathode material. In addition, because they contain a certain amount of lithium salt components from the electrolyte, they can also recharge the cathode active material during battery use, thereby improving the energy density and extending the life of the power battery.
[0094] As an optional embodiment of the present invention, the thickness of the coating layer is 5 to 50 nm. Typical but non-limiting coating layer thicknesses are 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm, etc.
[0095] As an optional embodiment of the present invention, the mass ratio of the composite additive to the positive electrode material is (1-50):100, preferably (5-20):100.
[0096] The mass ratio of composite additives to cathode materials should not be too high. A ratio exceeding 50:100 will deteriorate the properties of the interfacial films (SEI, CEI), interfere with the electrode reaction, exacerbate gas generation problems, and increase costs. Therefore, typical but non-limiting mass ratios of composite additives to cathode materials are 1:100, 5:100, 10:100, 12:100, 15:100, 18:100, 20:100, 22:100, 25:100, 30:100, 35:100, 40:100, 45:100, or 50:100, etc.
[0097] By further limiting the mass ratio of composite additives to cathode materials to a fixed range, it is beneficial to fully utilize the electrical properties and interfacial stability of composite cathode materials and reduce costs.
[0098] As an optional embodiment of the present invention, the Lewis base includes at least one of N-dimethylamide and N-acetylcaprolactam.
[0099] As an optional embodiment of the present invention, the N / B-containing compound includes compounds containing N and / or compounds containing B. The N-containing compound includes nitrile compounds (e.g., adiponitrile) or amine compounds (e.g., triethylamine). The B-containing compound includes borate esters (e.g., borate esters) and / or borane compounds.
[0100] According to a fourth aspect of the present invention, a method for preparing the above-mentioned composite cathode material is also provided, comprising the following steps: physically blending a composite additive and a cathode material, and then drying the mixture to form a powder, thereby obtaining the composite cathode material.
[0101] To improve the uniformity of mixing the cathode material and composite additives, wet blending can be used. Alternatively, besides directly preparing the composite cathode material using the aforementioned physical blending method, the composite additive can also be added during the cathode slurry preparation process, forming a slurry that is then coated onto the current collector. Alternatively, a micron-thickness layer of the composite additive can be sprayed onto an electrode sheet coated with the cathode active material, thereby forming a coating layer made of the composite additive on the surface of the cathode material. A schematic diagram of the preparation process is shown below. Figure 3 As shown.
[0102] According to a fifth aspect of the present invention, a positive electrode sheet is also provided, comprising a current collector and a positive electrode material layer formed on the surface of the current collector;
[0103] The positive electrode material layer includes a conductive agent, a binder, and the positive electrode material provided in the first aspect of the present invention or the composite positive electrode material provided in the third aspect of the present invention.
[0104] Given the advantages of the aforementioned cathode materials or composite cathode materials, cathode sheets containing them also possess the same advantages.
[0105] According to a sixth aspect of the present invention, a method for preparing the positive electrode sheet of the fifth aspect of the present invention is also provided, wherein the preparation is carried out by method one, method two or method three as follows:
[0106] Method 1: Prepare a slurry by combining a conductive agent, a binder, and a positive electrode material or composite positive electrode material, coat it on the surface of the current collector, and dry it to obtain a positive electrode sheet;
[0107] Method 2: The positive electrode material, composite additive, conductive agent and binder are made into a slurry, coated on the surface of the current collector, and dried to obtain the positive electrode sheet;
[0108] Method 3: Prepare a slurry by combining positive electrode material, conductive agent and binder, coat it on the surface of current collector, dry it, then spray a composite additive on the surface of the current collector positive electrode material layer, and dry it again to obtain the positive electrode sheet.
[0109] All of the above preparation methods can achieve stable preparation of positive electrode sheets.
[0110] As an optional embodiment of the present invention, when performing method three, the spraying method includes spraying, screen printing, and scraping. The spraying thickness is 0.5 to 10 μm, for example, 0.5 μm, 1 μm, 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, 9 μm, or 10 μm.
[0111] According to a seventh aspect of the present invention, a lithium-ion power battery is also provided, comprising the above-described positive electrode material, composite positive electrode material, or positive electrode sheet.
[0112] Given the advantages of the cathode material, composite cathode material, or cathode sheet described above in this invention, the compaction density, specific capacity, cycle performance, and safety performance of the lithium-ion power battery containing it are maintained at a good level.
[0113] As an optional embodiment of the present invention, the lithium-ion power battery includes a battery casing, a top cover, an electrode core, and an electrolyte. The electrolyte and the electrode core are sealed inside the battery casing. The electrode core is manufactured using a winding or stacking process, and the electrode core includes a positive electrode, a negative electrode, and a separator located between the positive and negative electrodes. The positive electrode includes a positive electrode current collector and a positive electrode material layer mainly made of positive electrode material or composite positive electrode material located on the positive electrode current collector.
[0114] The present invention will now be described in further detail with reference to specific embodiments and comparative examples.
[0115] Example 1
[0116] This embodiment provides a cathode material with the following general formula:
[0117] Li2(Ni a Co b Mn c ) 1-d M d O2·Mn x Fe y PO4·A;
[0118] Where a = 0.6, b = 0.1, c = 0.3, d = 0.01, M is element Nb, and Nb 5+It exists in ionic form; x = 0.6, y = 0.4, A is C (carbon coating).
[0119] That is, the cathode material is Li2(Ni 0.6 Co 0.1 Mn 0.3 ) 0.99 Nb 0.01 O2·Mn 0.6 Fe 0.4 PO4·C.
[0120] The preparation method of the positive electrode material in this embodiment includes the following steps:
[0121] Nickel-cobalt-manganese ternary precursors (particle size 3-5 μm) and lithium manganese iron phosphate precursors (particle size 100-200 nm) were mixed at a mass ratio of 0.6:0.4. Then, a first dopant (NbCl5) and a second dopant (glucose) were added. The first dopant accounted for 2.5±0.5% of the mass fraction of the nickel-cobalt-manganese ternary precursors, and the mass ratio of the first dopant to the second dopant was 0.6:0.4. The mixture was then sintered at 690-710℃ for 10 h in a helium atmosphere to obtain the cathode material.
[0122] The nickel-cobalt-manganese ternary material precursor was prepared by a co-precipitation method, including the following steps:
[0123] Nickel sulfate, manganese sulfate, and cobalt sulfate were added to deionized water to prepare a mixed solution with a Ni:Co:Mn molar ratio of 0.6:0.1:0.3. Ammonia (0.4 mol / L) and sodium hydroxide aqueous solution (1 mol / L) were bubbled into the mixed solution to adjust the pH of the reaction system to 11.5. The reaction was carried out at 40±2℃ and 580 rpm with stirring. Nitrogen gas was introduced as a protective gas during the reaction. After the reaction was completed, the solid product was washed with deionized water and dried at 100℃ to obtain the ternary material precursor Ni. 0.6 Co 0.1 Mn 0.3 (OH)2.
[0124] The preparation method of lithium manganese iron phosphate precursor includes the following steps:
[0125] Manganese source (manganese carbonate), iron source (iron phosphate), ammonium hydrogen phosphate and lithium salt (lithium carbonate) were mixed with a molar ratio of manganese carbonate, iron phosphate, ammonium hydrogen phosphate and lithium carbonate of 60%:40%:100%:50%. The mixing frequency of the high-speed mixer was 50 Hz and the mixing time was 30 min to obtain the lithium manganese iron phosphate precursor.
[0126] Example 2
[0127] This embodiment provides a cathode material with the following general formula:
[0128] Li2(Ni a Co b Mn c ) 1-d M d O2·Mn x Fe y PO4·A;
[0129] Where a = 0.55, b = 0.1, c = 0.35, d = 0.01, M is Al, and Al 3+ It exists in ionic form; x = 0.7, y = 0.3, A is Mg, and it exists in Mg form. 2+ It exists in ionic form;
[0130] That is, the cathode material is Li2(Ni 0.55 Co 0.1 Mn 0.35 ) 0.99 Al 0.01 O2·Mn 0.7 Fe 0.3 PO4·Mg.
[0131] The preparation method of the positive electrode material in this embodiment includes the following steps:
[0132] Nickel-cobalt-manganese ternary precursor (particle size 3-5 μm) and lithium manganese iron phosphate precursor (particle size 100-200 nm) were mixed at a mass ratio of 0.7:0.3. Then, a first dopant (Al2O3) and a second dopant (Mg(NO3)2) were added. The mass fraction of the first dopant in the nickel-cobalt-manganese ternary precursor was 2.5±0.5%, and the mass ratio of the first dopant to the second dopant was 0.7:0.3. The mixture was then sintered at 790-710℃ for 10 h in a helium atmosphere to obtain the cathode material.
[0133] Example 3
[0134] This embodiment provides a cathode material with the following general formula:
[0135] Li2(Ni a Co b Mn c ) 1-d M d O2·Mn x Fe y PO4·A;
[0136] Where a = 0.5, b = 0.1, c = 0.4, d = 0.01, M is B, and B is the denoted number of the numerators. 3+ The form exists; x = 0.8, y = 0.2, A is Cu, with Cu 2+ Form exists;
[0137] That is, the cathode material is Li2(Ni 0.5 Co 0.1 Mn 0.4 ) 0.99 B 0.01 O2·Mn 0.8 Fe 0.2 PO4·Cu.
[0138] The preparation method of the positive electrode material in this embodiment includes the following steps:
[0139] Nickel-cobalt-manganese ternary precursors (particle size 3-5 μm) and lithium manganese iron phosphate precursors (particle size 100-200 nm) were mixed at a mass ratio of 0.4:0.6. Then, a first dopant (B2O3) and a second dopant (Cu(NO3)2) were added. The first dopant accounted for 2.5±0.5% of the mass fraction of the nickel-cobalt-manganese ternary precursors, and the mass ratio of the first dopant to the second dopant was 0.4:0.6. The mixture was then sintered at 690-710℃ for 10 h in a helium atmosphere to obtain the cathode material.
[0140] Example 4
[0141] This embodiment provides a composite cathode material, including the cathode material provided in Embodiment 1 and a coating layer covering the surface of the cathode material;
[0142] The coating layer is mainly composed of composite additives, and the coating layer thickness is 20±5 nm. The composite additives include lithium bis(fluorosulfonyl)imide (LiFSI) and 2-allylphenoxytrimethylsilane (APTS), with a mass ratio of lithium bis(fluorosulfonyl)imide to 2-allylphenoxytrimethylsilane of 0.6:0.4.
[0143] The preparation method of the composite cathode material in this embodiment includes the following steps:
[0144] The cathode material and composite additives are mixed at a mass ratio of 100:10, and then dried to form powder, thus obtaining the composite cathode material.
[0145] Example 5
[0146] This embodiment provides a composite cathode material, except that the composition of the composite additive is adjusted. Specifically, the composite additive includes lithium bis(fluorosulfonyl)imide (LiFSI), 2-allylphenoxytrimethylsilane (APTS), and Lewis base (N-acetylcaprolactam). The mass ratio of lithium bis(fluorosulfonyl)imide, 2-allylphenoxytrimethylsilane, and Lewis base is 0.3:0.5:0.2. The remaining raw material ratios and preparation methods are the same as in Example 4.
[0147] Example 6
[0148] This embodiment provides a composite cathode material. Except for adjusting the composition of the composite additive, which includes lithium bis(fluorosulfonyl)imide (LiFSI) and Lewis base (N-acetylcaprolactam) with a mass ratio of 0.6:0.4, the other raw material ratios and preparation methods are the same as in Example 4.
[0149] Example 7
[0150] This embodiment provides a method for preparing a composite cathode material. Except that the cathode material and composite additives are mixed at a mass ratio of 100:15, and the thickness of the coating layer formed by the composite additives on the surface of the cathode material is 20±5nm, the specific composition of the other composite additives is the same as in Example 4.
[0151] Example 8
[0152] This embodiment provides a composite cathode material, including the cathode material provided in Embodiment 2 and a coating layer covering the surface of the cathode material;
[0153] The coating layer is mainly made of composite additives, and the coating layer thickness is 20±5 nm. The composite additives include 2-allylphenoxytrimethylsilane (APTS) and a nitrogen-containing compound (adiponitrile), with a mass ratio of 0.3:0.7 between 2-allylphenoxytrimethylsilane and the nitrogen-containing compound.
[0154] The preparation method of the composite cathode material in this embodiment includes the following steps:
[0155] The cathode material and composite additives are mixed at a mass ratio of 100:13, and then dried to form powder, thus obtaining the composite cathode material.
[0156] Example 9
[0157] This embodiment provides a composite cathode material, including the cathode material provided in Embodiment 3 and a coating layer covering the surface of the cathode material;
[0158] The coating layer is mainly composed of composite additives, and the coating layer thickness is 20±5 nm. The composite additives include lithium bis(fluorosulfonyl)imide (LiFSI) and 2-allylphenoxytrimethylsilane (APTS), with a mass ratio of lithium bis(fluorosulfonyl)imide to 2-allylphenoxytrimethylsilane of 0.4:0.6.
[0159] The preparation method of the composite cathode material in this embodiment includes the following steps:
[0160] The cathode material and composite additives are mixed at a mass ratio of 100:12, and then dried to form powder, thus obtaining the composite cathode material.
[0161] Comparative Example 1
[0162] This comparative example provides a cathode material with the general formula:
[0163] Li1(Ni a Co b Mn c ) 1-d M d O2;
[0164] Where a = 0.6, b = 0.1, c = 0.3, d = 0.01, M is element Nb, and Nb 5+ It exists in ionic form; that is, the cathode material is Li(Ni) 0.6 Co 0.1 Mn 0.3 ) 0.99 M 0.01 O2.
[0165] The preparation method of the comparative example cathode material includes the following steps:
[0166] A nickel-cobalt-manganese ternary precursor (particle size 3-5 μm) and a first dopant (NbCl5) were mixed, with the first dopant accounting for 2.5±0.5% of the mass fraction of the nickel-cobalt-manganese ternary precursor. The mixture was then sintered at 690-710℃ for 10 h in a helium atmosphere to obtain the cathode material.
[0167] The preparation method of the nickel-cobalt-manganese ternary material precursor is the same as that in Example 1.
[0168] Comparative Example 2
[0169] This comparative example provides a cathode material with the general formula:
[0170] LiMn x Fe y PO4·A;
[0171] Where x = 0.6, y = 0.4, and A is C (carbon coating layer), the cathode material is LiMn. 0.6 Fe 0.4 PO4·C.
[0172] The preparation method of the comparative example cathode material includes the following steps:
[0173] A lithium manganese iron phosphate precursor (particle size 100-200 nm) and a second dopant (glucose) were mixed, with the second dopant accounting for 1.5 ± 0.5% of the mass fraction of the lithium manganese iron phosphate precursor. The mixture was then sintered at 690-710 °C for 10 h in a helium atmosphere to obtain the cathode material.
[0174] The preparation method of the lithium manganese iron phosphate precursor is the same as that in Example 1.
[0175] Comparative Example 3
[0176] This comparative example provides a composite cathode material. Except for adjusting the composition of the composite additive in Example 4, that is, only lithium bisfluorosulfonyl imide (LiFSI) is used as an additive to coat the cathode material, the other raw material ratios and preparation methods are the same as in Example 4.
[0177] Comparative Example 4
[0178] This comparative example provides a composite cathode material. Except for adjusting the composition of the composite additive in Example 4, that is, using only 2-allylphenoxytrimethylsilane (APTS) as an additive to coat the cathode material, the other raw material ratios and preparation methods are the same as in Example 4.
[0179] To better illustrate the technical effects of the various embodiments and comparative examples, the following experimental examples are provided.
[0180] Experimental Example 1
[0181] The positive electrode materials or composite positive electrodes obtained in the various embodiments and comparative examples are used to fabricate a power square battery. This lithium-ion power battery includes a battery casing, an electrode core, and an electrolyte, with the electrode core and electrolyte sealed within the battery casing. The electrode core includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive and negative electrode sheets. The positive electrode includes a positive electrode current collector and positive electrode material located on the positive electrode current collector. The positive electrode material is the positive electrode material provided in the various embodiments and comparative examples of this invention. The negative electrode material includes a negative electrode current collector and negative electrode material located on the negative electrode current collector. The specific preparation method of this battery is as follows:
[0182] Preparation of the positive electrode sheet: The positive electrode material, conductive agent (SP and CNT, with a mass ratio of SP to CNT of 0.6:0.4), binder (PVDF) and solvent (NMP) prepared in each example or comparative example are mixed together, wherein the mass percentage of positive electrode active material, conductive agent and binder is 97.5%:1%:1.5%. The mixture is mixed for 3-5 hours using a planetary mixer or other high-speed mixer to prepare a positive electrode slurry. The positive electrode slurry is then coated onto a 12-13 μm aluminum foil using a transfer or extrusion coating method. The compaction density is selected according to the characteristics of each positive electrode main material (see Table 1 for details) to obtain the positive electrode sheet.
[0183] Preparation of the negative electrode: Conventional artificial graphite is used as the negative electrode material, combined with a conductive agent (SP), a dispersant (CMC), a binder (SBR), and water as a solvent to form a slurry. The mass percentages of the negative electrode active material, conductive agent, dispersant, and binder are 96.5%:1.0%:1.1%:1.5%. The slurry is coated onto a 4.5μm or 6μm copper foil using the same coating method as the positive electrode. After drying, it is rolled and pressed to a compaction density of 1.56–1.62 g / m³. 3 It is made into a negative electrode sheet;
[0184] Separator: 7μm PE base film, 2μm ceramic layer on one side (usually the positive electrode side), and 1.5μm adhesive coating on both sides. The adhesive coating is to make the electrode and the separator adhere more tightly during hot pressing, and can also increase the overall safety of the battery.
[0185] Electrolyte: 1M LiPF6+EC / DEC (1:1v / v);
[0186] Battery assembly: The positive electrode, negative electrode and separator are combined together to form the electrode core by a winding machine or stacking machine, then placed into the shell, packaged, and injected with electrolyte, and finally made into a lithium-ion power battery.
[0187] The compaction density, specific capacity, cycle performance, and safety of lithium-ion power batteries made from the cathode materials or composite cathodes obtained from the various embodiments and comparative examples were tested. The specific testing methods are as follows:
[0188] (1) Compacted density test method: During the rolling process, a small round piece is taken from the electrode, its mass is weighed, and the thickness of the round piece is measured. The calculation formula is: PD = (mass of small round piece - mass of foil) / area of small round piece / (thickness of small round piece - thickness of foil).
[0189] (2) Specific capacity measurement method: The finished battery is tested for 1 / 3C discharge capacity, specifically: 1 / 3C constant current charging to 3.65V, constant voltage 0.05C cutoff, standing for 30min, and 1 / 3C constant current discharging to 2.5V; at the same time, the mass of positive electrode active material contained in all positive electrode plates in a single cell is calculated, and the specific capacity = cell discharge capacity / mass of positive electrode active material in a single cell;
[0190] (3) Cyclic test: At 25℃, the battery is correctly installed on the Xinwei or Landian battery cell test cabinet and cyclically tested using the same step charging (average 2.2C) and 1C discharging test steps. Specifically, the battery is charged (average 2.2C) to 3.65V, left to stand for 30 minutes, and then discharged at 1C to 2.5V. It is left to stand for 30 minutes again. This cycle is repeated. When the battery capacity drops to 80% SOH, the battery life ends.
[0191] (4) Security Testing
[0192] Needle penetration test: First, fully charge the battery cell, then use a 5-8mm high-temperature resistant steel needle to penetrate the battery at a speed of 25±5mm / s, perpendicular to the wide surface. The steel needle remains in the battery and is observed for 1 hour. Record whether there is any expansion, leakage, smoke, fire or explosion.
[0193] Thermal runaway test: The finished battery was heated using a 600W heating plate. Heating was stopped when the thermal runaway judgment condition was triggered.
[0194] Thermal runaway determination criteria: When a) and c) or b) and c) occur, thermal runaway is determined;
[0195] a) The triggering object generates a voltage drop, and the drop value exceeds 25% of the initial voltage;
[0196] b) The temperature at the monitoring point reaches the maximum operating temperature specified by the manufacturer;
[0197] c) The temperature rise rate at the monitoring point, dT / dt, is ≥1℃ / s and lasts for more than 3s;
[0198] Observe for 1 hour and record whether there is expansion, leakage, smoke, fire or explosion.
[0199] The specific test results are shown in Table 1.
[0200] Table 1
[0201]
[0202]
[0203] The data in the table above shows that, compared to single ternary materials or lithium manganese iron phosphate materials, the cathode material prepared with the composite precursor has a compaction density, specific capacity, and cycle performance that are at the middle level of the two materials. However, compared to the former two, lithium manganese iron phosphate shows a significant improvement in overall performance, and its cycle performance and safety are significantly improved compared to ternary materials. Therefore, combining the advantages of both ternary materials and lithium manganese iron phosphate materials results in superior overall performance.
[0204] In addition, with the addition of composite additives, the cycle performance of the cathode material prepared by the composite precursor is further improved to ≥2000 cycles, and different types of additives, composite additives with different compositions and ratios all have a certain enhancement effect on the cycle performance of the cathode material.
[0205] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention shall be within the scope of protection of the pending claims of the present invention.
Claims
1. A composite cathode material, characterized in that, This includes a positive electrode material for lithium-ion power batteries, and a coating layer covering the surface of the positive electrode material; The general formula of the positive electrode material is: Li2(Ni a Co b Mr c ) 1-d M d O2 · Mn x Feb y PO4· A ; Where a+b+c=1, and 0<a≤0.6, 0<b≤0.1, 0<c<0.4, 0<d≤0.01, and M is selected from at least one of the elements Nb, Al, B or F; x+y=1, and 0<x<1, 0<y<1, x : y = (0.2~0.8) : (0.8~0.2); A is selected from at least one of Mg, Cu or C elements; The coating layer is mainly made of composite additives; the composite additives include lithium bis(fluorosulfonyl)imide salt and 2-allylphenoxytrimethylsilane; The mass ratio of the composite additive to the cathode material is (1-50):
100.
2. The composite cathode material according to claim 1, characterized in that, The composite additive includes lithium bisfluorosulfonylimide, 2-allylphenoxytrimethylsilane and Lewis base, or the composite additive includes lithium bisfluorosulfonylimide, 2-allylphenoxytrimethylsilane and N / B elements. The Lewis base includes at least one of N-dimethylamide and N-acetylcaprolactam; The N / B-containing compounds include compounds containing N and / or compounds containing B. The N-containing compounds include nitrile compounds and / or amine compounds. The nitrile compounds include adiponitrile, the amine compounds include triethylamine, and the B-containing compounds include borate esters and / or borane compounds.
3. The composite cathode material according to claim 1, characterized in that, The particle size of the positive electrode material is 5~30μm; And / or, the specific surface area of the positive electrode material is 1~40m². 2 / g; And / or, the cathode material is made of a nickel-cobalt-manganese ternary precursor, a lithium manganese iron phosphate precursor, and a first dopant containing element M and a second dopant containing element A.
4. The composite cathode material according to any one of claims 1-3, characterized in that, The positive electrode material is prepared using either method one or method two as follows: Method 1: Mix nickel-cobalt-manganese ternary precursor and lithium manganese iron phosphate precursor in a certain proportion to obtain a composite precursor; A first dopant containing element M and a second dopant containing element A are added to the composite precursor, followed by sintering to obtain the cathode material; or, Method 2: Add a first dopant containing element M during the preparation of nickel-cobalt-manganese ternary material precursor to obtain nickel-cobalt-manganese ternary material precursor doped with element M; In the process of preparing lithium manganese iron phosphate precursor, a second dopant containing element A is added to obtain an A-doped lithium manganese iron phosphate precursor. A nickel-cobalt-manganese ternary precursor doped with element M and a lithium manganese iron phosphate precursor doped with element A are mixed in a certain proportion and then sintered to obtain the cathode material.
5. The composite cathode material according to claim 4, characterized in that, In Method 1, the particle size of the nickel-cobalt-manganese ternary material precursor is 1~15μm; and / or, the particle size of the lithium manganese iron phosphate precursor is 100~400nm; And / or, in Method 1, the mass ratio of the nickel-cobalt-manganese ternary precursor to the lithium manganese iron phosphate precursor is (0.2~0.8): (0.8~0.2). And / or, in method one, the first dopant accounts for 1~2% of the mass fraction of the composite precursor; And / or, in method one, the mass ratio of the first dopant to the second dopant is (0.2~0.8):(0.8~0.2); And / or, in Method 2, the mass ratio of the nickel-cobalt-manganese ternary precursor doped with element M to the lithium manganese iron phosphate precursor doped with element A is (0.2~0.8):(0.8~0.2). And / or, in Method 2, the first dopant accounts for 2-3% of the mass fraction of the nickel-cobalt-manganese ternary precursor; And / or, in Method 2, the second dopant accounts for 1-3% of the mass fraction of the lithium manganese iron phosphate precursor; And / or, in Method 1 and Method 2, the sintering temperature is 600~800℃, the sintering time is 3~12h, and the sintering atmosphere is nitrogen or helium.
6. The composite cathode material according to claim 1, characterized in that, The thickness of the coating layer is 5~50 nm; And / or, the mass ratio of the composite additive to the cathode material is (5-20):
100.
7. The method for preparing the composite cathode material according to any one of claims 1-6, characterized in that, The process includes the following steps: physically blending the composite additive and the cathode material, and then drying them to obtain the composite cathode material.
8. A positive electrode sheet, characterized in that, Includes a current collector and a positive electrode material layer formed on the surface of the current collector; The positive electrode material layer includes: a conductive agent, a binder, and the composite positive electrode material according to any one of claims 1-6.
9. The method for preparing the positive electrode sheet according to claim 8, characterized in that, Prepared using one, two, or three of the following methods: Method 1: Prepare a slurry by combining the conductive agent, binder, and the composite positive electrode material, coat it on the surface of the current collector, and dry it to obtain the positive electrode sheet; Method 2: The positive electrode material, composite additive, conductive agent and binder are made into a slurry, coated on the surface of the current collector, and dried to obtain the positive electrode sheet; Method 3: Prepare a slurry by combining positive electrode material, conductive agent and binder, coat it on the surface of current collector to form a positive electrode material layer, then spray a composite additive on the surface of the positive electrode material layer and dry it to obtain a positive electrode sheet.
10. A lithium-ion power battery, characterized in that it comprises the composite cathode material according to any one of claims 1-6 or the cathode sheet according to claim 8.
Citation Information
Patent Citations
Mixed positive electrode material, positive plate using the same, and lithium ion battery
CN104300123A
Simple, convenient and efficient boron oxide coated high-nickel ternary positive electrode material and preparation method thereof
CN110729466A
High-nickel ternary positive electrode material and preparation method thereof
CN111244397A
Surface-modified ternary positive electrode material as well as preparation method and application thereof
CN115360345A
Semi-cyclized polyacrylonitrile gel coated high-voltage positive electrode material, preparation method thereof and application of semi-cyclized polyacrylonitrile gel coated high-voltage positive electrode material in solid-state battery
CN115663147A